Pengaruh Analisis Label Halal Dan Hargaterhadap Keputusan Membeli Produk Mie Samyang Bagi Remaja Diwilayah Kabupaten Kerinci - septiana, Rena; syarif, Dafiar; Wisaalam, Alex; Saleh, Muhammad Aunurrochim Bin Mas'ad (Jurnal Ilmiah Ekonomi Islam, 2024)
consumption of instant noodles from Korea, namely Samyang noodles, which is a country with a non-Muslim majority population, there are issues circulating regarding the halalness of Samyang noodle products which are considered to contain pork oil. This research aims to examine how the halal label factor influences buyer preferences, especially in the Kerinci area. The author uses quantitative research with a descriptive approach. In the research used as primary data were answers to questionnaires submitted to the people of Kerinci Regency. Meanwhile, secondary data is in the form of library literature, notes or historical reports that have been compiled in archives (documentary data) such as the Purchase Decision for Samyang Noodles in Generation Z, and processed using certain statistical methods. The scope of this research focuses more on variables that influence purchasing decision preferences. on imported food products. The influencing variables are halal labeling, income and product price. The results of this research are that the halal label variable has a significant effect on the decision to choose because the t-count value of ttable or 3.652, 199495 and the resulting significance is 0.001 - 0.05. So this means that the halal label variable has a significant effect on the decision to choose. "The halal label variable has a positive influence on the decision to choose teenagers from Kerinci Regency" is accepted. Meanwhile, the price variable does not have a significant effect on the decision to choose because the value of tcount or 1.718 1.99495 and the resulting significance is 0.90 0.05. So this means that the price variable does not have a significant effect on choosing decisions. "The price variable does not have a positive influence on the decision to choose teenagers from Kerinci Regency" and the percentage of influence between variables X1 and X2 on variable Y is 19.2%